ANALISIS KEBIASAAN BELAJAR SISWA BERPRESTASI PADA MATA PELAJARAN ILMU PENGETAHUAAN SOSIAL - Firda Rahmatulloh Hidayah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Analysis of the Learning Habits of Outstanding Students in Social Sciences (IPS) Subjects at Madrasah Ibtidaiyah Miftahul Ulum Ngoro Jombang. This study aims to find out the learning habits of outstanding students in Social Sciences subjects because these subjects have the potential to have gaps in research areas that have not been explored much compared to other subjects. In line with that, researchers see opportunities to make unique and valuable contributions in the field of Social Sciences subjects. This type of research is a descriptive qualitative research focused on three outstanding students in the subject of Social Sciences. The data source in this study is Social Science teachers using observation, interview, and documentation techniques. The results of the analysis conducted by the researcher showed that the learning habits of outstanding students in Social Sciences subjects generally have advantages in high semester average scores, attendance percentage, class rank, good behavior, and students participating in extracurricular activities related to the development of social soul potential. Madrasah Ibtidaiyah Miftahul Ulum Ngoro Jombang has a learning habituation program, material delivery techniques, task completion targets, and effective and efficient learning methods.